High-Pressure Supercritical CO2 Pretreatment of Apple Orchard Waste for Carbohydrates Production Using Response Surface Methodology and Method Uncertainty Evaluation - Lacrimioara Senila; Daniela Alexandra Scurtu; Eniko Kovacs; Erika Andrea Levei; Oana Cadar; Anca Becze; Cerasel Varaticeanu (Molecules, 2022)
This study’s objective was to separate cellulose, hemicellulose, and lignin after high-pressure supercritical carbon dioxide pretreatment for further valorization. The study investigated the supercritical carbon dioxide pretreatment of apple orchard waste at temperatures of 160–200 °C, for 15–45 min, at a pressure of 10 MPa. Response Surface Methodology (RSM) was used to optimize the supercritical process and to improve its efficiency. The change of functional groups during different pretreatment conditions was examined by Fourier transform infrared (FTIR) spectroscopy. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) confirmed the structural changes in the biomass structure before and after pretreatment. A new ultra-high performance liquid chromatography (UHPLC) coupled with an evaporative light scattering detector (ELSD) method was developed and validated for the determination of carbohydrates in the liquid fraction that resulted after pretreatment. The estimated uncertainty of the method ranged from 16.9 to 20.8%. The pre-treatment of high-pressure supercritical CO2 appears to be an effective and promising technique for the recovery of sugars and secondary by-products without the use of toxic solvents.